2023
DOI: 10.1051/0004-6361/202244667
|View full text |Cite
|
Sign up to set email alerts
|

A new method for age-dating the formation of bars in disc galaxies

Abstract: The epoch in which galactic discs settle is a major benchmark for testing models of galaxy formation and evolution but remains largely unknown. Once discs settle and become sufficiently self-gravitating, stellar bars are able to form; therefore, determining the ages of bars can shed light on the epoch of disc settling, and on the onset of secular evolution. Nevertheless, timing when the bar formed has proven challenging. In this work we present a new methodology for obtaining the bar age, using the star format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 103 publications
2
10
0
Order By: Relevance
“…This metallicity gradient agrees with the results obtained for two regions ∼20 pc to the Galactic east and west of the MWNSC, where the metallicity was found to decrease in comparison with the values found for the MWNSC (Feldmeier-Krause 2022). Moreover, similar metallicity gradients have been found in the central regions of nearby external barred spiral galaxies (Gadotti et al 2020;Bittner et al 2020;de Sá-Freitas et al 2023), pointing towards an inside-out growth of these nuclear stellar structures and indicating that they are connecting to the galactic bar.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This metallicity gradient agrees with the results obtained for two regions ∼20 pc to the Galactic east and west of the MWNSC, where the metallicity was found to decrease in comparison with the values found for the MWNSC (Feldmeier-Krause 2022). Moreover, similar metallicity gradients have been found in the central regions of nearby external barred spiral galaxies (Gadotti et al 2020;Bittner et al 2020;de Sá-Freitas et al 2023), pointing towards an inside-out growth of these nuclear stellar structures and indicating that they are connecting to the galactic bar.…”
Section: Discussionsupporting
confidence: 89%
“…The current paradigm for the formation of NSDs in barred spiral galaxies assumes that gas from the galactic disc is funnelled towards the innermost regions of the galaxy by a bar, growing NSDs from inside out and generating a gradient in the properties of their stellar population (e.g. Shlosman 2001;Sormani et al 2015;Seo et al 2019;Bittner et al 2020;de Sá-Freitas et al 2023). This is compatible with the detected kinematic and metallicity gradients and also with previous results on the MWNSD stellar population which show that this mechanism is also at play in the Milky Way (e.g.…”
Section: Formation Of the Mwnsd And Mwnscmentioning
confidence: 99%
See 1 more Smart Citation
“…So care has to be taken to differentiate older stars from those formed during bar formation (see e.g. de Sá-Freitas et al 2023a). Tepper-Garcia et al (2021), using a tailored N-body model of barred MW, suggested that the bar formed 3-4 Gyr ago.…”
Section: Introductionmentioning
confidence: 99%
“…As the gas around the bar within the corotation radius loses angular momentum, it flows inward. Piled-up gas in the central region ignites active star formation (SF; Hawarden et al 1986;Knapen et al 1995;Sheth et al 2005) to form nuclear disks that lead to the formation of inner bars in the nuclear disks and nuclear rings in some galaxies (e.g., Sormani et al 2018a;de Lorenzo-Cáceres et al 2019;Seo et al 2019;Gadotti et al 2020;Bittner et al 2021;de Sá-Freitas et al 2023a, 2023b. The gas transported to the central 100 pc may feed active galactic nuclei (AGN; e.g., Storchi-Bergmann & Schnorr-Müller 2019;Silva-Lima et al 2022;Garland et al 2023;Kolcu et al 2023), although the connection between bars and AGN is still controversial (e.g., Ho et al 1997;Knapen et al 2000;Laine et al 2002;Cisternas et al 2013;Cheung et al 2015;Neumann et al 2019;Zee et al 2023).…”
Section: Introductionmentioning
confidence: 99%